2018
DOI: 10.1007/s10115-018-1228-4
|View full text |Cite
|
Sign up to set email alerts
|

Community detection using multilayer edge mixture model

Abstract: A wide range of complex systems can be modeled as networks with corresponding constraints on the edges and nodes, which have been extensively studied in recent years. Nowadays, with the progress of information technology, systems that contain the information collected from multiple perspectives have been generated. The conventional models designed for single perspective networks fail to depict the diverse topological properties of such systems, so multilayer network models aiming at describing the structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 67 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Several variants have been developed by regarding modularity as a basic component or extending it to more general cases. 15,20,21 Another typical community detection method is stochastic block model, 22 which is a random graph model with planted communities. In addition, the generative models have been developed for community detection, 17,23 in which the community membership strength vectors are utilized to represent the community structure.…”
Section: Lower-order Community Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several variants have been developed by regarding modularity as a basic component or extending it to more general cases. 15,20,21 Another typical community detection method is stochastic block model, 22 which is a random graph model with planted communities. In addition, the generative models have been developed for community detection, 17,23 in which the community membership strength vectors are utilized to represent the community structure.…”
Section: Lower-order Community Detectionmentioning
confidence: 99%
“…One of the most widely adopted methods is modularity, 19 which partitions a network by maximizing the sum of the number of within‐community edges compared with the sum of the expected number of within‐community edges. Several variants have been developed by regarding modularity as a basic component or extending it to more general cases 15,20,21 . Another typical community detection method is stochastic block model, 22 which is a random graph model with planted communities.…”
Section: Related Workmentioning
confidence: 99%
“…Most of the current research on the community structure of multilayer networks is based on multiplexing networks, in which the community refers to the structure consisting of homogeneous nodes that are all more tightly connected in different layers 11 . Community detection on multilayer networks is usually implemented based on three methods: the algorithms based on modularity optimization 26 28 , network layer aggregation-based algorithms 29 , 30 , and dynamics-based algorithms 31 , 32 , among which modularity is the most widely used 4 , 33 . In 2010, Mucha et al 26 summarized the previous studies to obtain a modularity function for multilayer networks.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Pamfil et al 27 obtained various types of multilayer networks and demonstrated its effectiveness in synthetic and empirical networks. In 2019, Zhang et al 28 proposed a multilayer edge mixture model, and identifies different communities. Although the existing research on community detection of multiplexing networks has been relatively mature, it does not take into account the heterogeneity of nodes.…”
Section: Introductionmentioning
confidence: 99%